Investigation of SQL Clone on MVC-based Application - Fawwaz Ali Akbar; Siti Rochimah; Rizky Januar Akbar (Institut Teknologi Sepuluh Nopember, 2018)
Model-View-Controller (MVC) design pattern is design pattern that is suitable for interactive systems. MVC is adapted in desktop and web-based applications. Moreover, many frameworks are adapting MVC pattern. Each layer of MVC has a different function. The main function of the model layer is query to the database system that represented by SQL language. In software development, code duplication or code clone is a serious problem because it will impact on the maintenance process. Associated with model layer and code clone, clone detection approach that exists today is not effective to detect clones in the model layer represented by SQL language, because the definition of code clone is not suitable for SQL clone. SQL is declarative language that is different from the common programming language like C and Java. So, the definition of code clone must be adjusted with characteristic of SQL. In this research, we investigate the existence of SQL clone on MVC-based application and define the types of SQL clone. We define four types of SQL clone and they are confirmed exist in MVC-based application datasets that used in this research